Efficacy and safety of HAIC combined with tyrosine kinase inhibitors versus HAIC monotherapy for advanced hepatocellular carcinoma: a multicenter propensity score matching analysis - Miaomiao Yang; Xiongying Jiang; Huan Liu; Qingyu Zhang; Jing Li; Li Shao; Lei Zhao (Frontiers Media S.A., 2024)
PurposeThis study aimed to assess the clinical efficacy and safety of the combined approach involving hepatic arterial infusion chemotherapy (HAIC) and tyrosine kinase inhibitors (TKIs) for the treatment of advanced hepatocellular carcinoma (HCC).Patients and methodsIn this multicenter retrospective study conducted from January 2020 to December 2023, we reviewed advanced HCC patients who were treated either with HAIC alone or with a combination of HAIC and TKIs. To address initial disparities between the two groups, we employed propensity score matching (PSM). Tumor response evaluation was performed following RECIST 1.1 criteria. We compared survival outcomes, including overall survival (OS), progression-free survival (PFS), and objective response rate (ORR), between the two treatment groups. Safety assessments were conducted for all patients.ResultsFollowing the eligibility review, 138 patients underwent combined treatment with HAIC and TKIs (HT group), while 198 patients received HAIC monotherapy (HA group) and met the inclusion criteria for enrollment in this study. After PSM, 107 patients were assigned to each group. The HT group exhibited a longer median OS (18.0 versus 8.8 months; hazard ratio [HR], 0.52, p < 0.001) compared to the HA group. Median PFS was also longer in the HT group, although without statistical significance (6.0 versus 4.7 months; HR, 0.85, p = 0.265). The HT group demonstrated a higher ORR (41.1% versus 25.2%; p = 0.020). No significant differences were observed between the two groups in the incidence of all adverse events (AEs) or grade 3/4 AEs (any grade: 81.2% for HT versus 78.8% for HA, p = 0.68; grade 3/4: 18.1% for HT versus 13.6% for HA, p = 0.29). Importantly, all AEs were manageable and acceptable. Notably, no grade 5 AEs occurred in either group.ConclusionCombination therapy involving HAIC and TKIs effectively prolonged survival in advanced HCC patients. It represented a preferable alternative to HAIC monotherapy, with manageable safety.